Advancements in Poly(ionic liquid) composites with carbon nanomaterials - Hui Li; Jie Gao; Zhiyong Li; Yan Zhang; Jun Zhang; Shiguo Zhang (Advanced Industrial and Engineering Polymer Research)
Carbon nanomaterials have become essential in modern daily life. Their porous nature and good electrical conductivity are critical for composite applications. However, their inherent van der Waals forces and π-π interactions often result in spontaneous aggregation, which significantly hinders the uniform dispersion of carbon materials in polymer matrices. Establishing interactions between poly(ionic liquid) (PIL) and carbon materials ensures excellent compatibility. Integrating carbon materials with PIL markedly enhances mechanical strength, electrical conductivity, and thermal stability, benefiting the electronics, energy storage, and automotive industries. A thorough understanding of the physical and chemical properties of PILs is crucial for tailoring composite materials to specific applications, enhancing processing capabilities, and boosting performance. This article reviews recent advancements in PIL composites incorporating carbon nanomaterials and outlines future challenges in their development.